Practices of handing over note as an effort in maintaining continuity - Yahya, Anis; Idris, Khairuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Handover note is a document created by a person who is about to leave the position or organization, either temporarily or permanently, which serves as a guidance to facilitate the next successor to carry out his/her duties more effectively and efficiently in maintaining continuity. It is a very important communication tool to ensure the business runs smoothly without or with minimal issues occurring as a result of the work transition and replacement or change of employees. In public sector, handing over note is a requirement for any leaving staff but not at most of government-linked company or private sector. The aim of this study is to gain a better understanding of the concept, status and the importance of handing over notes, particularly at the corporate level. This qualitative study captured the perceptions of five managerial employees of UDA Holdings Berhad who experienced and involved in the handing over note. Data was collected through series of in-depth interviews, review of documents, and observations of the current practice. The findings showed that the concept of handing over note is not something new at UDA. It has been seen as a document of status report and expectation, a description of job function and responsibilities, a parting ritual and a transmission of authority. However, the practice of it at UDA is far from satisfactory. It is in dire need of a systematic process, varied in practice and has no legal authority and implication. Few initiatives suggested having a systematic process, a standard handover note, and policy development, review or alignment to make it legally binding and become organizational culture. Handing over note is important at both individual and organization level as a hallmark of accountability, a parameter for evaluation to measure the staff’s achievements and performance, an anchor for organization stability, rail track leading to organization goals, transmission and maintenance of organizational culture and treasure chest for organization history and memory.